Collision of Fundamental Human Rights and the Right to Health Access During the Novel Coronavirus Pandemic - José Luiz Gondim dos Santos; Paulo André Stein Messetti; Fernando Adami; Italla Maria Pinheiro Bezerra; Paula Christianne G. G. Souto Maia; Elisa Tristan-Cheever; Elisa Tristan-Cheever; Luiz Carlos de Abreu; Luiz Carlos de Abreu; Luiz Carlos de Abreu; Luiz Carlos de Abreu (Frontiers Media S.A., 2021)
Introduction: COVID-19 requires governmental measures to protect healthcare system access for people. In this process, the collision of fundamental rights emerges as a crucial challenge for decision-making.Policy Options and Implications: This policy review analyzes selected articles by the PubMed searcher about extreme measures taken in several countries during precedent pandemics and the current pandemic, and selects hard decisions relating to the exceptional measures taken by judicial departments in Brazil, connecting them to the "collision of fundamental rights and law principles." The collision of rights and principles imposed on decision makers a duty to provide balanced rights, and to adopt the enforcement of some rights prioritization. Ethical concerns were also verified in this field involving rights limitations. During a pandemic, the importance of extreme measures to protect health rights and healthcare systems is instrumental for focused, fast, and correct decision making to avoid loss of life and the collapse of healthcare systems. The main goals of this research are to discuss the implications and guidelines for public health decision making, the indispensable ethical and legal aspects for safeguarding health systems and the lives of people, and the respect of the Justice principle and of fundamental health and dignity rights. We conclude that COVID-19 justifies the prioritization of collective and individual health access rights. Acceptable standards of fundamental rights restrictions are established at the constitutional and international levels and must be enforced by rules and governmental action, to ensure fast and accurate decision making during a pandemic. Freedom rights exercises must be linked to solidarity for the realization of social welfare, for the health rights of all individuals and for health systems to function well during a pandemic.Actionable Recommendations: All individuals are free and equal, therefore social exclusion is prohibited. Institutions must consider social inequalities when discussing public health measures and be guided by ethical standards, by law principles, and rules recognized by constitutional and international law for the benefit of all during a health pandemic.Conclusions: Collective and individual health rights prevail over the collision of rights when facing pandemic occurrences, case by case, in health systems protection, based on the literature, on precedent pandemics and on legitimate Public Health efforts.